A comparison of phonetic convergence in conversational interaction and speech shadowing. (July 2018) - Pardo, Jennifer S.; Urmanche, Adelya; Wilman, Sherilyn; Wiener, Jaclyn; Mason, Nicholas; Francis, Keagan; Ward, Melanie
Highlights: Phonetic convergence is subtle and highly variable across talkers and settings. Previous studies have investigated phonetic convergence separately in speech shadowing and conversational interaction tasks. The present study examines the relationship between phonetic convergence in speech shadowing and conversational interaction with a large group of talkers who provided speech in both settings. Results found that phonetic convergence across these settings is only moderately related in male talkers and unrelated in female talkers. Patterns of phonetic convergence challenge accounts of automatic perception-production integration. Abstract: Phonetic convergence is a form of variation in speech production in which a talker adopts aspects of another talker's acoustic–phonetic repertoire. To date, this phenomenon has been investigated in non-interactive laboratory tasks extensively and in conversational interaction to a lesser degree. The present study directly compares phonetic convergence in conversational interaction and in a non-interactive speech shadowing task among a large set of talkers who completed both tasks, using a holistic AXB perceptual similarity measure. Phonetic convergence occurred in a new role-neutral conversational task, exhibiting a subtle effect with high variability across talkers that is typical of findings reported in previous research. Conversational phonetic convergence did not differ by talker sex on average, but relationships between speech shadowing and conversational convergence differed according to talker sex, with female talkers showing no consistency across settings in their relative levels of convergence and male talkers showing a modest relationship. These findings indicate that phonetic convergence is not directly compatible across different settings, and that phonetic convergence of female talkers in particular is sensitive to differences across different settings. Overall, patterns of acoustic–phonetic variation and convergence observed both within and between different settings of language use are inconsistent with accounts of automatic perception-production integration.